2015
DOI: 10.4172/2169-0022.1000204
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature Heat Treatment (80°C) Effect on the Electrochemically Synthesized CuInTe2 Thin Films for Energy Harvesting Applications

Abstract: We have investigated the effect of low-temperature (80ºC) post-deposition heat treatment onto CuInTe 2 (CIT) thin films prepared by one-step electrochemical technique. Aqueous precursor solution consisting ionic species of Cu, In and Te with pH 4.0 was used for the growth of CIT layers. The deposition potential was optimized using cyclic voltammetry. Conventional three-electrode geometry was used to electrodeposit CIT thin films onto CdS substrates. The structural, optical, morphological, compositional and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Lakhe et al studied the solar cell performance of electrodeposited CuInTe 2 [128,130,131]. The CuInTe 2 film was deposited on a FTO glass substrate on which a CdS layer was pre-produced via chemical bath deposition (CBD).…”
Section: Copper Indium Tellurides (Cit)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lakhe et al studied the solar cell performance of electrodeposited CuInTe 2 [128,130,131]. The CuInTe 2 film was deposited on a FTO glass substrate on which a CdS layer was pre-produced via chemical bath deposition (CBD).…”
Section: Copper Indium Tellurides (Cit)mentioning
confidence: 99%
“…The solar cell was configured as FTO/CdS/CuInTe 2 /Au, i.e., an inverted structure, in which electrons and holes diffuse to the FTO electrode and metal electrode, respectively. It was found that CuInTe 2 deposited through the electrolyte with a pH value of 2 was copper rich, leading to a relatively high solar-to-power conversion efficiency, 4.13% [128], whereas CuInTe 2 deposited with the electrolyte, which pH = 4, was however copper poor (or, indium rich) and, consequently, gave rise to somewhat low efficiencies ranging from 3.8% [130] to 4.01% [131].…”
Section: Copper Indium Tellurides (Cit)mentioning
confidence: 99%